Folk Liquid Manures for Sustainable Horticulture - Solanki, Shivendu Pratap Singh; Telkar, S. G.; Hota, Debashish; Kant, Kamal; Dey, Joy Kumar (International Journal of Economic Plants, 2015)
Folk liquid mannures are potent source for macro and micro nutrients, plant growth promoting factors and immunity enhancer. These possess pesticide and fungicidal properties. However, efficacy of these manures is influenced by inputs used and method of preparation. These can be used for seed or seedling treatment, enhancing decomposition, improving soil fertility and productivity. These are fertigation compatible through drip irrigation systems. In Sanskrit, Panchagavya means a combination of five products obtained from cow. When suitably mixed and used, these have miraculous effects. Panchagavya is used in different forms such as foliar spray, soil application along with irrigation water, seed or seedling treatment etc. For foliar spray 3% concentration is being used by organic farmers. Panchagavya was an important one that enhanced the biological efficiency of crop and the quality of fruits and vegetables production. It also increases the soil fertility. Sanjibani is a preparation having cow dung and cow urine. It helps to improve soil fertility and enhance crop productivity and quality of product and also working as a pest-repellent. This paper reviews the preparation, uses and benefits of such formulation in detail.